Clinical trial to test the efficacy of melatonin in COVID‐19. Issue 3 (8th August 2020) - Acuña‐Castroviejo, Dario; Escames, Germaine; Figueira, Juan C.; de la Oliva, Pedro; Borobia, Alberto M.; Acuña‐Fernández, Carlos
Abstract: The pharmacological properties of melatonin are well known. However, there is noticeable the lack of clinical trials that confirm the efficacy, security, absence of side effects in the short and long term, and the effective doses of melatonin. This point is especially important in diseases with high morbidity and mortality including COVID‐19. There is not treatment for COVID‐19, and several anti‐inflammatory and antiviral molecules are being tested, and different vaccines are in preparation. Although the SARS‐CoV‐2 pandemic is apparently improving, it is expected new resurges next fall. Thus, looking for an effective treatment of COVID‐19 is mandatory. Melatonin has significant anti‐inflammatory, antioxidant, and mitochondrial protective effects, and its efficacy has been demonstrated in multiple experimental models of disease and in a clinical trial in sepsis. Because COVID‐19 courses with a severe septic response, multiple reviews proposing melatonin as a treatment for COVID‐19 have been published. Nevertheless, there is a lack of experimental and clinical data on the use of melatonin on SARS‐CoV‐2 infection. Accordingly, we designed a clinical trial with an injectable formulation of melatonin for intravenous perfusion in ICU patients suffering from COVID‐19 that has been just approved by the Spanish Agency of Medicines and Medical Devices (AEMPS). The trial will allow by the first time understand the doses and efficacy of melatonin against COVID‐19.